Adhesion Force Measurement of Mica surface using AFM - Subedi, Chetan; Lamichhane, S K (Himalayan Physics, 2011)
AFM is a tool to study the surface topography and associated molecular forces in real space image. AFM force-distance spectroscopy is the platform on which one can quantify atomic or molecular interactions and hence provide information that is critical to understand potential energy surface of mica through the measurement of pull-off force. Keywords: AFM; Force distance curve; Nanoscale; Pull off force The Himalayan Physics Vol.2, No.2, May, 2011 Page: 71-72 Uploaded Date: 1 August, 2011